2008
DOI: 10.2116/analsci.24.839
|View full text |Cite
|
Sign up to set email alerts
|

Topographic Trace-Elemental Analysis in the Brain of Wistar Rats by X-ray Microfluorescence with Synchrotron Radiation

Abstract: Knowledge about the spatial distribution and the local concentration of trace elements in tissues is of great importance, since trace elements are involved in many biological functions of living organisms. However, there are few methods available to measure the spatial (two (three)-dimensional) elemental distribution in animal brain. X-ray microfluorescence with synchrotron radiation is a multielemental mapping technique, which was used in this work to determine the topographic of iron, zinc and copper in coro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 29 publications
(35 reference statements)
0
10
0
2
Order By: Relevance
“…According to Jackson et al (2006), the complexity of sample preparation and instrumental techniques, the expense of instrument, and the number of analyte ions that can be determined are the important criteria for selecting a surface analytical technique. Based on literatures reported previously, besides the abovementioned fluorescence microscopic techniques, proton-induced X-ray emission (PIXE) (Thong et al, 1999;Robertson et al, 2002;Augustyniak et al, 2006;Reinert et al, 2007), microprobe synchrotron X-ray fluorescence (ASXRF) (Ide-Ektessabi, Kawakami, & Watt, 2004;Flinn et al, 2005;Serpa et al, 2008), synchrotron X-ray absorption spectroscopy (SXAS) (Collingwood et al, 2005;Mikhaylova et al, 2005), secondary ion mass spectrometry (SIMS) (Burns, 1981;Clerc, Fourre, & Fragu, 1997;Aranyosiova et al, 2008), and laser ablation inductively coupled plasma mass spectrometry (LA-ICP-MS) (Feldmann, Kindness, & Ek, 2002;Becker et al, 2005aBecker et al, ,b, 2007aBecker et al, ,b, 2008aJackson et al, 2006;Dobrowolska et al, 2008;Sela et al, 2007;Zoriy et al, 2008) are the most widely applied surface analytical techniques for elemental imaging in brain tissues.…”
Section: Surface Analytical Techniquesmentioning
confidence: 99%
“…According to Jackson et al (2006), the complexity of sample preparation and instrumental techniques, the expense of instrument, and the number of analyte ions that can be determined are the important criteria for selecting a surface analytical technique. Based on literatures reported previously, besides the abovementioned fluorescence microscopic techniques, proton-induced X-ray emission (PIXE) (Thong et al, 1999;Robertson et al, 2002;Augustyniak et al, 2006;Reinert et al, 2007), microprobe synchrotron X-ray fluorescence (ASXRF) (Ide-Ektessabi, Kawakami, & Watt, 2004;Flinn et al, 2005;Serpa et al, 2008), synchrotron X-ray absorption spectroscopy (SXAS) (Collingwood et al, 2005;Mikhaylova et al, 2005), secondary ion mass spectrometry (SIMS) (Burns, 1981;Clerc, Fourre, & Fragu, 1997;Aranyosiova et al, 2008), and laser ablation inductively coupled plasma mass spectrometry (LA-ICP-MS) (Feldmann, Kindness, & Ek, 2002;Becker et al, 2005aBecker et al, ,b, 2007aBecker et al, ,b, 2008aJackson et al, 2006;Dobrowolska et al, 2008;Sela et al, 2007;Zoriy et al, 2008) are the most widely applied surface analytical techniques for elemental imaging in brain tissues.…”
Section: Surface Analytical Techniquesmentioning
confidence: 99%
“…Postmortem studies have shown that copper levels are increased in Aβ plaques in the brains of patients with AD . Furthermore, the content and distribution of copper in the brain changes with aging and neurodegenerative diseases . Recent studies have also demonstrated that abnormal copper homeostasis in the brain is involved in the progression of AD and possibly other neurodegenerative diseases .…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies from this laboratory have demonstrated that the BBB serves as the major route for the transport of Cu into the brain parenchyma, while the BCB mainly contributes to maintain the Cu homeostasis in the brain by exporting excess Cu from the CSF to the blood (Choi and Zheng, 2009 ; Zheng and Monnot, 2012 ; Fu et al, 2014 ). Once entering the brain, the Cu content and spatial distribution are uneven (Becker et al, 2005 ; Lech and Sadlik, 2007 ; Dobrowolska et al, 2008 ; Davies et al, 2013 , 2014 ; Ramos et al, 2014 ), which also vary among different species (Waggoner et al, 2000 ; Olusola et al, 2004 ; Jackson et al, 2006 ), and change during the development, with age and in neurodegenerative conditions (Palm et al, 1990 ; Tarohda et al, 2004 ; Serpa et al, 2008 ; Wang et al, 2010 ; Ramos et al, 2014 ). Age-related increase in brain Cu content was observed in mouse (Wang et al, 2010 ), rat (Palm et al, 1990 ), and bovine (Zatta et al, 2008 ).…”
Section: Introductionmentioning
confidence: 99%